L’histoire du malade. Croisement de deux anthropologies - Pauline Labey (L'Atelier du CRH)
The history of those who suffer from illness may integrate anthropology in two ways. First, anthropology can be used as method and a mode of questioning. In writing history of the sick, the historian must grasp a particular physiological situation and its social consequences in everyday life. He must question a society about its relationship with the body when it is affected by illness, and about what happens when an individual departs from the norm of health. Second, a history of the sick can use anthropology as a discourse, the product of a given period. In this case, anthropology is used as a subject of research. Combining practice and discourse, it is possible to apprehend individual consequences of an illness-event. This dual use of anthropology may clarify the spiritual and institutional consequences of illness in the central Middle Ages.